Study on UV-crosslinking process of diane-epoxy resin/poly(tetrahydrofurane) divinyl ether system II. Influence of epoxy resin and poly- -(tetrahydrofurane) divinyl ether content on photocrosslinking of the diane epoxy/poly- -(tetrahydrofurane) divinyl ether system - Phi Hung, Dao; Anh Hiep, Nguyen; Van Phuc, Mac (Vietnam Journal of Science and Technology, 2016)
The effect of diane-epoxy resin (DE) and poly(tetrahydrofuran) divinyl ether (DVE) content on the photo crosslinking reaction of the DE/DVE system with triarylsulfonium salt (TAS) as photo-initiator were investigated. The results showed that increasing DVE content improved some of physico-mechanical properties of photocrosslinked coatings although the relative hardness and the speed of photocrosslinking reaction reduced. The results of the changes of functional groups, relative hardness and gel fraction as well as the physico-mechanical properties of UV-cured coatings based on DE/DVE/TAS system illustrated that suitable mass ratio of constituents was 80/20/5. The UV-cured coating based on the system DE/DVE/TAS = 80/20/5 cross-linked completely after 3.6 seconds UV-exposure and having good physico-mechanical properties: impact resistance reached 180 kg.cm; the flexibility obtained 1mm; the adhesion and relative hardness were point 1 and 0.7, respectively.